Factors of Profitability: Evidence from the Serbian Manufacturing Sector (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2022)
This paper aims to investigate factors of profitability in the manufacturing sector in the Republic of Serbia. The research is based on the sample of 220 observations of financial statements of listed companies on the Belgrade stock exchange from sector C – manufacturing during 2017-2020. Profitability was measured as a return on assets (ROA) and return on equity (ROE) being the two most common ratios. Primarily, the descriptive statistics of ROA and ROE were conducted. The results showed that manufacturing companies achieve a positive rate of profitability but at a low level (ROA is 0,0263 and ROE is 0,0595). Furthermore, two regression models were conducted to investigate which internal factors significantly affected ROA and ROE as dependent variables. The independent variables were set: fixed assets ratio, size, current ratio, leverage, and growth. Results of the first model showed that size, current ratio, and growth have a significant positive impact on ROA, while leverage significantly negatively impacts ROA. Results of the second model show that size and growth have a significant positive impact on ROE, while leverage negatively impacts it.